Personality as a Correlate of Accentedness: The Case of Formal Setting Without Pronunciation-Focused Instruction - Małgorzata Baran-Łucarz (Research in Language)
The main goal of the study reported in this paper was to verify whether the Big Five personality traits can be considered correlates of accentedness in a setting deprived of pronunciation-focused instruction. Each trait was measured among 58 English majors in Poland, who were just beginning their education at the university, by the means of the Polish version of Goldberg’s measure, i.e. IPIP-BFM-50. The levels of the traits were correlated with the participants’ degree of accentedness assessed by 2 judges on a 9-point Likert scale with the use of a reading task. The quantitative data were supplemented by interviews with 10 participants representing high and low levels of accentedness, which allowed to diagnose their motivation, attitudes towards the sound of English, pronunciation self-perceptions, and strategies applied in autonomous learning. The quantitative data showed a weak correlation only between Openness to experience and accentedness, which was further moderated by the other above-mentioned individual learner differences. Additionally, the qualitative outcomes suggested the importance of Agreeableness, which was found to be very high or high among learners with the lowest levels of accentedness.